The association between self-acceptance, emotion regulation, and treatment adherence self-efficacy among adolescents with HIV in Liangshan prefecture, China: a cross-sectional study - Dan Tan; Wenxi Zhong; Li Ma; Jing Cheng; Xianjun Mao; Xi Zhang; Jian Tang; Song Fan; Bianchuan Cao; Yanhua Chen (BMC Public Health)
Abstract Background Achieving viral suppression through effective treatment adherence is critical for adolescents with HIV; however, the role of treatment adherence self-efficacy—an individual’s confidence in their ability to consistently follow antiretroviral therapy (ART) regimens—remains under-explored among Chinese adolescents. This gap is particularly concerning given the United Nations’ “95-95-95” targets to end the AIDS epidemic by 2030. Objective The aim of this study is to investigate the treatment adherence self-efficacy levels of Yi ethnic adolescents with HIV in a county in Liangshan Prefecture, and to explore the association between self-acceptance, emotion regulation, and treatment adherence self-efficacy. Methods A cross-sectional study was conducted in a county of Liangshan Prefecture from November 2023 to March 2024. A convenience sampling method was used to select 205 participants. Multiple linear regression models were employed to examine the relationships between demographic variables, self-acceptance, emotion regulation and treatment adherence self-efficacy. A p-value < 0.05 was considered statistically significant. Results The study involved 205 participants (response rate: 96%) with an average age of 14.08 years. The mean ± standard deviation (SD) treatment adherence self-efficacy score of the study participants was 73.09 (± 16.37). Treatment adherence self-efficacy was significantly associated with factors such as residence [β = -0.174, 95% CI = (-13.841, -2.260)], occupation [β = 3.234, 95% CI = (7.061, 29.137)], and age [β = 0.312, 95% CI =(0.742, 2.502)]. In addition, self-acceptance and emotion regulation were positively correlated with treatment adherence self-efficacy. For each unit increase in self-acceptance, treatment adherence self-efficacy improved [β = 0.157; 95% CI =(0.081, 0.892)], and for each unit increase in emotion regulation, treatment adherence self-efficacy also improved [β = 0.314; 95% CI = (0.288, 0.724)]. Conclusions This study highlighted that several factors, including place of residence, occupation, age, self-acceptance, and emotion regulation, were significantly associated with treatment adherence self-efficacy among adolescents with HIV. Notably, self-acceptance and emotion regulation were positively correlated with treatment adherence self-efficacy. Enhancing treatment adherence self-efficacy in this population could be achieved by focusing on improving self-acceptance and emotion regulation. Furthermore, interventions aimed at increasing treatment adherence self-efficacy should prioritize rural areas, non-student populations, and younger adolescents, as these groups tend to exhibit lower adherence self-efficacy. Tailored interventions that address the specific needs of these subgroups could contribute to improved health outcomes and more effective HIV management among adolescents.